Provenance of Weeden Island "sacred" and "prestige" vessels: implications for specialized ritual craft production. Issue 2 (4th May 2017) - Wallis, Neill J.; Cordell, Ann S.; Harris-Parks, Erin; Donop, Mark C.; Hall, Kristen
ABSTRACT: Weeden Island mortuary ceremonialism united distinct cultures across the Late Woodland social landscape. The Weeden Island pottery series is central to recognizing regional ceremonial parity, with prestige (elite) and sacred (cult) wares showing strong similarities among distant sites. Finely made vessels and their ostensibly shamanistic themes led archaeologists to consider the liturgical and political roles of ritual specialists, whose tasks might have included vessel manufacture in centralized locations. This research evaluates the prospect of craft specialization and centralized production of sacred and prestige wares through comparisons of the provenance of vessels from three Florida localities: Palmetto Mound (8LV2), the mounds at Melton (8AL5, 8AL7), and McKeithen (8CO17). Results of Neutron Activation Analysis and petrographic analysis show that the majority of the sampled vessels were made far from the mounds in which they were deposited, from a variety of locations but especially within the area between Kolomoki and the Tallahassee Hills. We argue that production was not centralized but may have been specialized to the extent that an integrated ritual network was necessary to coordinate rules of manufacture and use that were evidently observed by all participants.